EXP OPTIMIZING HUMAN RESOURCE MANAGEMENT FUNCTIONS IN COMPANIES: RECRUITMENT AND JOB ASSESSMENT STRATEGIES FOR EXPATRIATE EMPLOYEES: Research Study on the Placement of Indonesian Citizen Expatriates in Multinational Companies - Santoso, Amelia Sofie; Fadillah, Nur Aini; Fitri, Dinar Shabina Al; Sandi, Mario Dwi; Mario, Mario Dwi Sandi (Jurnal Administrasi Bisnis, 2024)
This study aims to explain the strategy of optimizing the human resource management function in a company, focusing on the recruitment strategy and performance assessment of expatriate employees. This study takes a case study on the placement of Indonesianexpatriates in a multinational company operating in Malaysia. This type of research is descriptive research with a qualitative approach. Data collection methods used include interviews and literature studies. Interviews were conducted with expatriate employees, namely Indonesian citizens working in Malaysia. The results of the study indicate that the recruitment strategy used involves a selection process that considers cultural adaptability, international work experience, and technical competence. Expatriate employee performance assessment is carried out through target-based performance measurements that are adjusted to the local cultural context. Factors that influence expatriate performance include adaptability, interpersonal communication, and support from the company in dealing with cross-cultural obstacles. This study also identifies the main challenges faced by expatriates, such as differences in work culture,stereotypes, and language barriers, which affect their performance and interactions with local employees. Cross-cultural integration and training strategies are important elements in optimizing the human resource management function in multinational companies.